Pharmacological intervention of HIV-1 maturation - Dan Wang; Wuxun Lu; Feng Li (Elsevier, 2015)
Despite significant advances in antiretroviral therapy, increasing drug resistance and toxicities observed among many of the current approved human immunodeficiency virus (HIV) drugs indicate a need for discovery and development of potent and safe antivirals with a novel mechanism of action. Maturation inhibitors (MIs) represent one such new class of HIV therapies. MIs inhibit a late step in the HIV-1 Gag processing cascade, causing defective core condensation and the release of non-infectious virus particles from infected cells, thus blocking the spread of the infection to new cells. Clinical proof-of-concept for the MIs was established with betulinic acid derived bevirimat, the prototype HIV-1 MI. Despite the discontinuation of its further clinical development in 2010 due to a lack of uniform patient response caused by naturally occurring drug resistance Gag polymorphisms, several second-generation MIs with improved activity against viruses exhibiting Gag polymorphism mediated resistance have been recently discovered and are under clinical evaluation in HIV/AID patients. In this review, current understanding of HIV-1 MIs is described and recent progress made toward elucidating the mechanism of action, target identification and development of second-generation MIs is reviewed.